1999
DOI: 10.1063/1.369599
|View full text |Cite
|
Sign up to set email alerts
|

Electric field dependence of piezoelectric properties for rhombohedral 0.955Pb(Zn1/3Nb2/3)O3– 0.045PbTiO3 single crystals

Abstract: The electric field dependence of the piezoelectric properties of rhombohedral 0.955Pb(Zn1/3Nb2/3)O3–0.045PbTiO3 crystals were investigated as a function of orientation with respect to the prototypic (cubic) axes. For 〈111〉 oriented fields, depolarization and subsequent domain reorientation resulted in an apparent maximum in the piezoelectric coefficients occurring at ∼5 kV/cm, followed by nonhysteretic dij saturation, indicating a single domain state under bias. By extrapolation, single domain values for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(72 citation statements)
references
References 4 publications
5
64
0
1
Order By: Relevance
“…Previous investigations of Pb͑Zn 1/3 Nb 2/3 )O 3 -4.5%PbTiO 3 crystals have yielded similar anisotropic values for Y ͗001͘ and Y ͗111͘ . 16 However, in our study, in the ͑011͒ plane, an unusual isotropy of Y was also found, where Y ͗001͘ ϭY ͗110͘ ӶY ͗111͘ . Averaging of anisotropic elastic constants in ceramics can lead to a large difference between Y of the ceramic and crystal forms.…”
Section: Introductionmentioning
confidence: 44%
“…Previous investigations of Pb͑Zn 1/3 Nb 2/3 )O 3 -4.5%PbTiO 3 crystals have yielded similar anisotropic values for Y ͗001͘ and Y ͗111͘ . 16 However, in our study, in the ͑011͒ plane, an unusual isotropy of Y was also found, where Y ͗001͘ ϭY ͗110͘ ӶY ͗111͘ . Averaging of anisotropic elastic constants in ceramics can lead to a large difference between Y of the ceramic and crystal forms.…”
Section: Introductionmentioning
confidence: 44%
“…Following the same argument in previous studies [1][2][3][4][5][6][7][8][9], we treat the [0 0 1] poled PZN-PT and PMN-PT single crystals as pseudo-tetragonal with 4mm domain pattern symmetry. The fourfold axis is along the poling direction, i.e., [0 0 1] direction of parent cubic system.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…Due to the extremely attractive application potential of these new single crystal piezoelectric materials in making ultrasonic transducers and piezoelectric actuators, extensive studies have been conducted on these crystals in recent years [1][2][3][4][5][6]. For both fundamental study and device design purposes, it is necessary to measure the complete set of elastic, piezoelectric and dielectric constants of these crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric and piezoelectric properties have been well characterized [19,20] and the massive anisotropy in response between 111 and 001 E-field poled crystals in the rhombohedral phase underscored. The piezoelectric d 33 > 2000 pC/N, k 33 > 92%, ε 33 T > 5,000 for 001 E-field rhombohedral phase crystal at composition close to the MPB are of strong practical interest.…”
Section: Alternative Single Crystal Systemsmentioning
confidence: 99%
“…For m3m, it is simple to show that the volume strain s v in all possible ferroelectric phases is given by Measurements by Park [20] show that over the linear strain range up to 35 Kv/cm the volume change in PZN 0.95.5 PT 0.045 is less than 0.05%. Taking as a first aproximation s v = 0, the polarization vector is just rotating under field and from fig.…”
Section: Alternative Single Crystal Systemsmentioning
confidence: 99%